Culture industry - Steinert, Heinz (Polity, 2003)
The term a culture industrya has been a key reference point in the critical literature on culture and the media ever since the classic chapter in Horkheimer and Adornoa s Dialectic of Enlightenment, yet until now there has been little attempt to update the analysis for the present day. In this innovative new book, Heinz Steinert applies the concept of culture industry to contemporary cultural forms and demonstrates its relevance for the twenty--first century. Unravelling Horkheimer and Adornoa s complex prose, Steinert sets out to explain precisely what is meant by the term a culture industrya . Writing in a clear and engaging style, he provides an accessible exposition of the key themes and concepts. This close textual analysis is combined with wide--ranging case studies showing how the concept of culture industry can be used to approach more recent cultural phenomena. Examining contemporary film, pop music and art, as well as dating agencies and the paparazzi, Steinert reveals the ways in which culture is commodified today. This is an original book that provides a fresh critical perspective on culture and the media. It will be essential reading for students of media and cultural studies, sociology and of the humanities in general.